PHF5A promotes colorectal cancerprogression by alternative splicing of TEAD2 - Yue Chang; Yulu Zhao; Liya Wang; Meijuan Wu; Chenglong He; Mengxi Huang; Zengjie Lei; Jiahe Yang; Siqi Han; Bibo Wang; Yanyan Chen; Chao Liu; et al. (Elsevier, 2021)
Dysregulated alternative splicing (AS) plays critical roles in driving cancer progression, and the underlying mechanisms remain largely unknown. Here, we demonstrated that PHF5A, a component of U2 small nuclear ribonucleoproteins, was frequently upregulated in colorectal cancer (CRC) samples and associated with poor prognosis. PHF5A promoted proliferation and metastasis of CRC cells in vitro and in vivo. Transcriptomic analysis identified PHF5A-regulated AS targets and pathways. Particularly, PHF5A induced TEAD2 exon 2 inclusion to activate YAP signaling, and interference of TEAD2-L partially reversed the PHF5A-mediated tumor progression. Pharmacological inhibition of PHF5A using pladienolide B had potent antitumor activity. Collectively, these data revealed the oncogenic role of PHF5A in CRC through regulating AS and established PHF5A as potential therapeutic target.